PENYELESAIAN SENGKETA RUMAH TANGGA PERSPEKTIF TAFSIR BUYA HAMKA TERHADAP SURAT AN-NISA AYAT 34 – 35 - Oktorinda, Tri (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
This research raises the problem of Household Dispute Resolution Perspective Tafsir Buya Hamka  Against Surat An Nisa Verse 34 - 35. The purpose of this study to describe the Settlement of Household Dispute Perspective Tafsir Buya Hamka  Against Surat An Nisa Verse 34 - 35. The method used  in research Library research. The results  of this study that by overcoming the  wickedness of the  wife by giving advice  and  guidance, separating the  bed  or silent  in bed,  and  a resuscitate punch. In the case  of husband nusyuz, Islam offers peace, could  with the initiative of the wife of both parties introspection each  other. In order to maintain a home network, being mutually legowo  to give the best for the couple is a recommendation. If indeed both parties  are no longer able to be reconciled, you should  take a way by using a good 3rd party is willing to solve the problem.